Service quality and consumer purchasing intention toward online ticketing: an empirical study in Iran - Nikhashemi, Seyed Rajab; Haque, A. K. M. Ahasanul; Yasmin, Farzana; Khatibi, Ali (IACSIT Press, 2012)
This study gives a reports on e-service quality and consumer purchase intention toward online ticketing, in this research we tried to find out why some group of people have stick to traditional channel for their purchase and some other group prefer to use online channel as a tool of shopping. The outcome of this study demonstrated a comprehensively integrated framework that can utilize by the policy makers and business enterprises to understand significant relationships among dimensions of e-service quality, perceive of usability, perceived risk and internet knowledge. Also this research considered how price perception and online trust can be utilized to understand the consumer purchase intention toward online ticketing. In addition the other factor which has made our study sophisticated is e-service quality which has significant effect on consumer purchase intention behavior to have online purchase. However further research is needed to examine these factors in Iran with the additional samples before generalization can be made. Upon of that, it is also necessary to review consumer purchasing behavior in making decision to use internet as mean of purchasing online rather than the traditional way.